Interregional migration of business owners: who moves and how does moving affect firm performance?. Issue 4 (3rd April 2019) - Niedomysl, Thomas; Källström, John; Koster, Sierdjan; Östh, John
ABSTRACT: Business owners play an important role in driving regional economic growth, and policy-makers seek to attract and retain such entrepreneurs by most means available. This paper analyses migration patterns, the factors that influence the propensity to move and assesses the relationship between firm performance and individual migration both before and after the move. The results show that (1) known explaining variables of migration propensity also hold for business owners; (2) owners with more substantial firms in terms of turnover and employees are more geographically anchored; and (3) a simultaneous move of residence and firm has an unclear impact on firm performance.